The Diversity, Equity, and Inclusion in a Global Perspective - Alaverdov, Emilia (Journal of Education Culture and Society, 2023)
Aim. The goal of the paper is migration processes in the context of globalisation leading to the erosion of cultural identity and the emergence of many heterogeneous cultures in many countries. Modern countries, where traditional societies with minor inclusions of another culture of European origin, have turned into multicultural communities, in which there are many scenarios for intercultural dialogue and multiculturalisation, including such negative options as xenophobia and racism, highlighting that one of the consequences of the multicultural approach in Europe has been a retreat into closed cultural communities. Methods. During the working process on the paper we applied the main methods of social and political studies such as the comparative analysis method; empirical methods; the method of observation; evaluation method and methods of content analysis. The paper is based on empirical research materials, articles, reports, research, and books. Results and conclusion. By way of conclusion, we can say that Muslim migrants who arrive in Europe, for the most part, do not hurry to integrate into the local society. Compared to the local population, they wear different clothes, have different habits, and profess a different religion. All this sets one to consider them y as “others,” as strangers, which, under certain conditions, can lead to a feeling of fear or hostility (Alaverdov, 2020). The fact that Muslims maintain respect for their traditions is often seen by residents of their host countries as a sign of disrespect for local traditions.